Core spliceosomal Sm proteins as constituents of cytoplasmic mRNPs in plants - Hyjek‐Składanowska, Malwina; Bajczyk, Mateusz; Gołębiewski, Marcin; Nuc, Przemysław; Kołowerzo‐Lubnau, Agnieszka; Jarmołowski, Artur; Smoliński, Dariusz Jan (The Plant journal : for cell and molecular biology, 2020)
SUMMARY In recent years, research has increasingly focused on the key role of post‐transcriptional regulation of messenger ribonucleoprotein (mRNP) function and turnover. As a result of the complexity and dynamic nature of mRNPs, the full composition of a single mRNP complex remains unrevealed and mRNPs are poorly described in plants. Here we identify canonical Sm proteins as part of the cytoplasmic mRNP complex, indicating their function in the post‐transcriptional regulation of gene expression in plants. Sm proteins comprise an evolutionarily ancient family of small RNA‐binding proteins involved in pre‐mRNA splicing. The latest research indicates that Sm could also impact on mRNA at subsequent stages of its life cycle. In this work we show that in the microsporocyte cytoplasm of Larix decidua, the European larch, Sm proteins accumulate within distinct cytoplasmic bodies, also containing polyadenylated RNA. To date, several types of cytoplasmic bodies involved in the post‐transcriptional regulation of gene expression have been described, mainly in animal cells. Their role and molecular composition in plants remain less well established, however. A total of 222 mRNA transcripts have been identified as cytoplasmic partners for Sm proteins. The specific colocalization of these mRNAs with Sm proteins within cytoplasmic bodies has been confirmed via microscopic analysis. The results from this work support the hypothesis, that evolutionarily conserved Sm proteins have been adapted to perform a whole repertoire of functions related to the post‐transcriptional regulation of gene expression in Eukaryota. This adaptation presumably enabled them to coordinate the interdependent processes of splicing element assembly, mRNA maturation and processing, and mRNA translation regulation, and its degradation. Significance Statement The study reports the cyclic occurrence of cytoplasmic mRNP accumulations enriched in canonical Sm proteins but not in other spliceosomal components in Larix decidua microsporocytes. Based on transcriptomic analysis, 222 mRNAs were identified as cytoplasmic partners for Sm proteins, which were linked to many gene ontology terms. The results presented show that S‐bodies constitute newly described cytoplasmic domains involved in the post‐transcriptional regulation of highly expressed transcripts, particularly in cells in which mRNA synthesis occurs in transcriptional bursts.